KONSEP GURU DALAM PERSPEKTIF MUNIF CHATIB - Tri Sugiarti (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2018)
The educational system in Indonesia still tends to generalize the standard of intelligence of one student with other students with the assessment of narrow methods and parameters, namely the cognitive aspect only. Circumstances like this would certainly adversely affect the development of the potential possessed by students, because basically every student has a different kind of intelligence diferent. This research is a library research of data collection is done by analyzing books by Munif Chatib, interview and collect data from other relevant. The approach of this research is pedagogik psikologi. The data analysistechnique used is the content analysis continued on the descriptive analytics. Research result show: first the teacher must eliminate negative label to student before entering into class, teacher have to have view and mindset which assume every child is champion. Both teachers should look at the broader competencies of the students, based on three proportional cognitive, psychomotor, and affective abilities. The thirdis willing to to keep learning. The fourth continues to explore the student’s abilities. The fifth taught in a fun way. The six teachers are the facilitators. The seven teachers teach by heart.Key Word: Teacher, education, Munif Chatib